Animasi 2D Sejarah Perjuangan Rakyat Bali pada Perang Puputan Badung - Ketut Gus Oka Ciptahadi; I Putu Arista Narendra Darma; Ni Wayan Setasih (STMIK Bina Nusantara Jaya Lubuk Linggau, 2026)
The Puputan Badung event of 1906 is one of the most heroic moments in the history of the Balinese people's struggle against Dutch colonialism. However, the lack of accessible information sources and the absence of engaging visual media have made this story less known among the younger generation. This study aims to visualize the story of the Balinese people's struggle in the form of 2D animation as an engaging, easy-to-understand, and widely accessible historical learning medium through a website. The method used in this research is MDLC (Multimedia Development Life Cycle), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The result of this research is an animated video with a duration of 11 minutes and 55 seconds, distributed through digital platforms and a specially designed website. Evaluation was conducted using black box testing for the website and a Likert scale questionnaire for the animation, targeting high school/vocational school students as the main audience, and achieved a score of 83.89%, which falls into the “very good” category. Based on the test results, this media is considered effective in delivering historical information and in increasing young people's interest in Bali’s local history. Keywords: Puputan Badung, 2D Animation, Balinese History, MDLC, Learning Media